The comparative immunogenicity of human and porcine factor VIII in haemophilia A mice - Healey, John F.; Parker, Ernest T.; Barrow, Rachel T.; Langley, Travis J.; Church, William R.; Lollar, Pete (Thrombosis and Haemostasis, 2009)
Inhibitory antibodies to factor VIII (FVIII inhibitors) are the most significant complication in the management of haemophilia A. The immunogenicity of FVIII may be driven in part by structural determinants within the FVIII molecule itself. Regions of nonidentity between human and porcine FVIII possibly could drive differential immune responses. The goal of this study was to compare the overall antibody response and levels of antibodies to the individual FVIII domains in naïve haemophilia A mice immunised with human or porcine FVIII. Haemophilia A mice were immunised with human or porcine FVIII using a protocol that mimics human clinical use. Inhibitor and total anti-FVIII antibody titers were measured and the domain-specificity of antibodies from 1,759 anti-FVIII hybridomas was determined. The overall immunogenicity of human and porcine FVIII was similar but significant differences in domain recognition were discovered. Anti-A2 and anti-C2 antibodies constituted the majority of inhibitors in both the human and porcine FVIII groups, similar to inhibitors that develop in humans.The proportions of anti-A2 or anti-C2 antibodies were not significantly different between the two groups. However, the specific inhibitory activity of anti-A2 antibodies was higher in the human FVIII group. Additionally, proportion of anti-C1 antibodies was significantly higher in the human FVIII group. In contrast, anti-A3 antibodies were more common in the porcine FVIII group.The differential immune response to human and porcine FVIII suggests that it may be possible to reduce the immunogenicity of FVIII by mutagenesis of the A2, A3 and C1 domains.
Keywords: Factor VIII; haemophilia therapy; coagulation inhibitors